A Comparative Study on the Post-treatment Process of Sputtered SnO2 Nanorod OAD Films - Kaewyou, Thitiporn; Pangpaiboon, Nampueng; Lertvanithphol, Tossaporn; Jaruwongrungsee, Kata; Patthanasettakul, Viyapol; Pogfay, Tawee; Limwichean, Saksorn; Horprathum, Mati (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
The effects of single-step and two-step annealing and O2 plasma treatments on SnO2 slanted nanorods (SNR) films fabricated using DC magnetron sputtering and oblique angle deposition (OAD) was investigated in this study. The FE-SEM, AFM, and GI-XRD analyses demonstrate that both treatment approaches significantly influenced the film tilt angle, thickness, and surface morphology. After annealing, nanorod separation improved, surface roughness increased, and crystallinity was enhanced, particularly in the (110), (101), and (211) planes of the tetragonal rutile phase. In contrast, oxygen plasma treatments caused etching, reduced film thickness, and formed nano-necks at the tips of the slanted nanorods, leading to a reduction in crystallinity. Additionally, two-step treatments, particularly annealing followed by plasma treatment, achieved the best crystallinity while minimizing the etching effects of plasma. Finally, the optical properties, investigated using a UV–Vis–NIR spectrophotometer, demonstrated a progressive decrease in average transmittance within the visible region, from 86% to 79%, corresponding to the increasing number of post-treatment steps. In parallel, the optical bandgap was also found to decrease with additional treatments, shifting from 4.14 eV to 3.84 eV. The results highlight the importance of structural modifications in SnO2 SNR films, as they directly influence film properties and enhance the potential for advanced optoelectronic device applications.